Financial realities for farms in the European Union: Relationships between farming and governmental interactions within the Triple Helix concept - Vítor Jo\~ao Pereira Domingues Martinho (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2018)
The objective of this study is to analyse the financial realities for the farming sector in European Union countries and their relationships with agricultural investment and public structural subsidies, from a perspective of farming- and governmental relationships as part of the Triple Helix approach. Firstly, the statistical information available within the Farm Accountancy Data Network for the former twenty seven European Union countries, related with the main items of the accounting balance sheet was investigated. Secondly, various financial indicators were calculated to analyse the principal financial constraints in these farms and finally, these findings with the levels of investment and structural support were reported. As a main conclusion, more adjusted structural policies in the European Union will be needed, taking these microeconomic contexts into account.
Keywords: E22; M41; O52; Q12; 330; Farming sector; Structural subsidies; Accountancy information; European Union; Triple Helix